(untitled) (Bangladesh Medical Journal Khulna, 2018)
Fanconi Anemia (FA) is a rare potentially life threatening autosomal recessive disorder characterized by progressive pancytopenia, multiple congenital anomalies with multiple type of cancer risk. The presentation may be variable but typical presentation make the diagnosis easy. Diagnosis of FA can be confirmed by chromosome break study which is regarded as the gold standard diagnostic test for FA. Only one case report of FA had been published from Bangladesh till now. Here is the second variety of FA. If FA is confirmed then a set of preventive strategy can be applied. On the other hand misdiagnosis may lead to mismanagement which is not uncommon. Bang Med J (Khulna) 2017; 50 : 46-48